Being in Virtual Worlds: How Interaction Environment and Touch Shape Embodiment in Immersive Experiences - Desnoyers-Stewart, John; Antle, Alissa N.; Riecke, Bernhard E. (ACM CHI, 2025)
Embodiment is an everyday experience that typically goes unnoticed. While we often take it for granted, with the adoption of virtual reality (VR) technology, embodiment in virtual bodies and worlds has become an important consideration for designers of immersive experiences. To date, the VR design community has primarily considered embodiment in terms of body ownership over a synchronized visual representation. In this paper, we construct an interactional framework of virtual embodiment, beginning by revisiting what it really means to be “embodied.” Our framework reconnects embodiment and presence in virtual environments founded in Dourish’s concept of embodied interaction and Heidegger’s Dasein or “being-in-the-world.” We discuss how embodiment, fundamentally rooted in past and present interactions, changes our understanding of body ownership and its extension into VR. Integrating theories from VR research, philosophy, HCI, and psychology we uncover the complex interplay of interaction, environment, and touch in shaping embodied experiences. We present a novel framework for understanding embodiment in VR rooted in interaction, enabling designers to create more immersive and meaningful virtual worlds.
Keywords: Riecke; Riecke_2025; alissa-antle; bernhard-riecke; conferencePaper; john-desnoyers-stewart; proj--being-in-VR